2016
DOI: 10.1155/2016/9349437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renal Ischemic Postconditioning on Myocardial Ultrastructural Organization and Myocardial Expression of Bcl-2/Bax in Rabbits

Abstract: We investigated the cardioprotective effect of renal ischemic postconditioning (RI-PostC) and its mechanisms in a rabbit model. Rabbits underwent 60 min of left anterior descending coronary artery occlusion (LADO) and 6 h of reperfusion. The ischemia-reperfusion (IR) group underwent LADO and reperfusion only. In the RI-PostC group, the left renal artery underwent 3 cycles of occlusion for 30 seconds and release for 30 seconds, before the coronary artery was reperfused. In the RI-PostC + GF109203X group, the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Renal blood flow needs to be blocked in renal transplantation, nephrolithotomy and surgical resection of renal tumors and other complex surgeries, and renal reperfusion after blood flow blocking can cause renal damage ( 10 ). Numerous studies have shown that ischemia-reperfusion injury may be related to the production of oxygen free radicals, adenine nucleotide metabolic disorders and cell apoptosis ( 11 ). Drugs (ulinastatin and propofol), low temperature, preconditioning and postconditioning can play a protective role in ischemia-reperfusion injury, and all these methods can be used to reduce ischemia-reperfusion injury to the kidneys ( 12 – 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Renal blood flow needs to be blocked in renal transplantation, nephrolithotomy and surgical resection of renal tumors and other complex surgeries, and renal reperfusion after blood flow blocking can cause renal damage ( 10 ). Numerous studies have shown that ischemia-reperfusion injury may be related to the production of oxygen free radicals, adenine nucleotide metabolic disorders and cell apoptosis ( 11 ). Drugs (ulinastatin and propofol), low temperature, preconditioning and postconditioning can play a protective role in ischemia-reperfusion injury, and all these methods can be used to reduce ischemia-reperfusion injury to the kidneys ( 12 – 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-reperfusion injury may be related to the synthesis of proinflammatory mediators, production of oxygen free radicals, and cell apoptosis [2]. The mechanisms that lead to the synthesis of proinflammatory and apoptotic mediators have been in-vestigated in recent years [3].…”
mentioning
confidence: 99%